2016
DOI: 10.1158/1541-7786.mcr-15-0281
|View full text |Cite
|
Sign up to set email alerts
|

Defining ATM-Independent Functions of the Mre11 Complex with a Novel Mouse Model

Abstract: The Mre11 complex (Mre11, Rad50 and Nbs1) occupies a central node of the DNA damage response (DDR) network, and is required for ATM activation in response to DNA damage. Hypomorphic alleles of MRE11 and NBS1 confer embryonic lethality in ATM deficient mice, indicating that the complex exerts ATM independent functions that are essential when ATM is absent. To delineate those functions, a conditional ATM allele (ATMflox) was crossed to hypomorphic NBS1 mutants (Nbs1ΔB/ΔB mice). Nbs1ΔB/ΔB Atm−/− hematopoietic cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Whereas pro-B cells (CD43 + ) from Nbs1 -/mid8vav were increased ( Figure 2E), the levels of B220 + cells decreased beginning at the pre B stage when immunoglobulin heavy chain rearrangement commences (Alt et al, 2013;Teng and Schatz, 2015) to the immature B cell stage (CD43 -), and IgM + mature B cells were virtually undetectable ( Figure 2F-H). These data suggest that Nbs1 -/mid8vav cells are unable to resolve DSBs formed during the course of B cell development, reminiscent of previous analyses of lymphocyte development in Mre11 complex mutants (Balestrini et al, 2016;Callen et al, 2007;Deriano et al, 2009;Helmink et al, 2009). The hematopoietic phenotype of Nbs1 -/mid8vav mice is distinct from that of Atm -/-vav in all respects ( Figure 1E…”
Section: Nbs1 -/Mid8vav and Hematopoiesissupporting
confidence: 64%
See 1 more Smart Citation
“…Whereas pro-B cells (CD43 + ) from Nbs1 -/mid8vav were increased ( Figure 2E), the levels of B220 + cells decreased beginning at the pre B stage when immunoglobulin heavy chain rearrangement commences (Alt et al, 2013;Teng and Schatz, 2015) to the immature B cell stage (CD43 -), and IgM + mature B cells were virtually undetectable ( Figure 2F-H). These data suggest that Nbs1 -/mid8vav cells are unable to resolve DSBs formed during the course of B cell development, reminiscent of previous analyses of lymphocyte development in Mre11 complex mutants (Balestrini et al, 2016;Callen et al, 2007;Deriano et al, 2009;Helmink et al, 2009). The hematopoietic phenotype of Nbs1 -/mid8vav mice is distinct from that of Atm -/-vav in all respects ( Figure 1E…”
Section: Nbs1 -/Mid8vav and Hematopoiesissupporting
confidence: 64%
“…The Mre11 complex is required for hematopoiesis (Adelman et al, 2009;Balestrini et al, 2016;Callen et al, 2007;Reina-San-Martin et al, 2005). We asked whether the Nbs1 mid8 gene product had sufficient residual function to allow hematopoietic stem cells expressing only Nbs1 mid8 to support hematopoietic development.…”
Section: Nbs1 -/Mid8vav and Hematopoiesismentioning
confidence: 99%
“…To determine whether the rescue fragments would sustain viability in vivo , we assessed their ability to support the differentiation of lymphocytes. Previous analyses indicated that the Mre11 complex is required for lymphocyte development (Balestrini et al, 2015; Callen et al, 2007; Deriano et al, 2009; Reina-San-Martin et al, 2004). Nbs1 F/F mice were crossed to vavCre mice, which express cre recombinase in hematopoietic stem cells (HSCs) (Stadtfeld and Graf, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The MRN complex is a multifunctional enzyme conglomerate known to activate cell cycle checkpoints when sensing DNA breakage (Stracker and Petrini, 2011). In addition to a critical role in ATM function and double strand break repair, MRN is also implicated in suppression of lymphomagenesis (Balestrini et al, 2015) and regulating metastatic breast cancers (Gupta et al, 2013). In humans, MRE11A mutations cause an ataxia-telangiectasia-like disease, with considerable variability in clinical phenotypes (Taylor et al, 2015).…”
Section: Discussionmentioning
confidence: 99%